PENGARUH MOTIVASI DAN PERHATIAN KELUARGA TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA SEKOLAH DASAR - Joko Subando (MAMBA'UL 'ULUM, 2022)
This study aims to (1) find out the relationship of motivation on learning achievement of Islamic religious education, (2) to know the relationship of family attention to the learning achievement of Islamic education, (3) to know the influence of motivation and attention to the learning achievement of Islamic education in elementary school students. The study used positivism approach, conducted in Elementary School of Daar El Dzikir Bulu Sukoharjo with population of 234 and 24 samples. Technique of collecting data by observation, interview, documentation and spreading of questionnaire. Before the data were analyzed using linear regression, with F test and T test, the data were tested for conformity with classical assumptions such as normality, heterogenity, and autocorrelation. The results showed that there is no significant relationship between motivation to achievement learning, there is a significant relationship between the attention of parents to achievement learn and there is no significant influence between motivation and attention of parents to learning achievement of Islamic education in elementary school students